A cobalt-based metal–organic framework electrodeposited on nickel foam as a binder-free electrode for high-performance supercapacitors. (14th June 2022) - Yu, Yue; Han, Yan; Cui, Jian; Wang, Caiyun
Abstract : Co-MOF/NF has been prepared by cathodic electrodeposition using highly active cobalt as a surface modifier, and shows improved capacitance performances. Abstract : A cobalt-based metal–organic framework (Co-MOF) has been in situ grown on nickel foam (NF) by cathodic electrodeposition using a highly active cobalt surface modifier to enable uniform nucleation and tight growth of the Co-MOF. The macroscopic (NF) and microscopic structures (rodlike crystals) construct a hierarchical structure with good conductivity, providing sufficient electroactive sites and highways of electrolyte diffusion and electron transfer. When used as a binder-free electrode (Co-MOF/NF) for supercapacitors, it shows improved electrochemical performance with a high areal specific capacitance of 1536 mF cm −2 at 1 mA cm −2, excellent rate capability and good cycling stability, which confirms that the Co-MOF/NF has potential applications in energy storage and conversion fields.